OUTCOME OF OPTICAL INTERNAL URETHROTOMY IN URETHRAL STRICTURE: A PROSPECTIVE STUDY - Yunas, Muhammad; Ullah, Amir Amaan; Rehman, Atta ur; Khan, Waseem Yaar; Khan, Irfan Ullah; Ali, Mian Naushad (Journal of Postgraduate Medical Institute, 2011)
Objective: This study was conducted to assess the role of optical internal urethrotomy in patients with urethral stricture. Material and Methods: This study was conducted at Khyber Teaching Hospital Peshawar and Khattak Medical Centre Peshawar from March 2003 August 2003. Male patients were selected from the patients presenting with history of urethral stricture regardless of age and etiology. Patients with neurogenic bladder, enlarged prostate, bladder stone or meatal stricture were excluded. All patients were investigated with standardized protocol. Optical internal urethrotomy was performed in all patients and they were followed at monthly interval. The success of procedure was evaluated by grading the patient response as excellent, good, acceptable and poor. Results: Out of 30 patients, 11(36.66%) were between 20 and 30 years of age. The most common cause was trauma 21(70%).The most common site was bulbous urethra in 22 (73.33%) cases followed by membranous urethra in 4(13.33%) cases. In patients with stricture of less than 1cm, 21/25(84%) showed excellent response while in stricture of more than 1cm, 1/5(20%) showed excellent response. Excellent results were seen in patients with stricture in 18/22 (81.81%) cases of bulbous urethra. Nine (30%) cases showed minor post operative complications with no major complications. No recurrence was reported in 3 months follow up. Conclusion: Internal optical urethrotomy is a safe first line treatment in urethral stricture independent of the cause. It has low morbidity for the working class people.